2018
DOI: 10.1038/s41419-018-0922-1
|View full text |Cite
|
Sign up to set email alerts
|

HGF-mediated crosstalk between cancer-associated fibroblasts and MET-unamplified gastric cancer cells activates coordinated tumorigenesis and metastasis

Abstract: Cancer-associated fibroblasts (CAFs) are important components of tumor stroma and play a key role in tumor progression. CAFs involve in crosstalk with tumor cells through various kinds of cytokines. In the present study, we screened hepatocyte growth factor (HGF) as a cytokine predominantly originating from CAFs. CAFs-derived HGF was found to promote MET-unamplified gastric cancer (GC) proliferation, migration, and invasion through the activation of HGF/c-Met/STAT3/twist1 pathway. It also activated interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 49 publications
1
66
0
Order By: Relevance
“…Previous study have reported that high HGF level in pre-operative serum represent the invasive growth of tumor foci and c-MET positive immunostaining in gastric cancer tissues indicate the tumor with larger diameter, advanced lymphatic vessel invasion and lymph node metastasis [24], the above conclusion was supported by the outcome of our previous work and our colleagues, both of which shown HGF enhance tumorigenesis of gastric cancer via a paracrine pattern [2,3,25]. We found that HGF-c-MET are enriched in MAPK signaling pathway, PI3K-Akt signaling pathway, JAK-Stat3 signaling pathway and biological process of positive regulation of cell migration, and these analyses had been validated in our prior study, which found PI3K/ Akt and ERK1/2 signaling pathway participated in the process of HGF-dependent vascularization in gastric cancer and Jak2/Stat3 signaling pathway involved in the process of HGF-dependent migrant and invasive promotion of gastric cancer.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Previous study have reported that high HGF level in pre-operative serum represent the invasive growth of tumor foci and c-MET positive immunostaining in gastric cancer tissues indicate the tumor with larger diameter, advanced lymphatic vessel invasion and lymph node metastasis [24], the above conclusion was supported by the outcome of our previous work and our colleagues, both of which shown HGF enhance tumorigenesis of gastric cancer via a paracrine pattern [2,3,25]. We found that HGF-c-MET are enriched in MAPK signaling pathway, PI3K-Akt signaling pathway, JAK-Stat3 signaling pathway and biological process of positive regulation of cell migration, and these analyses had been validated in our prior study, which found PI3K/ Akt and ERK1/2 signaling pathway participated in the process of HGF-dependent vascularization in gastric cancer and Jak2/Stat3 signaling pathway involved in the process of HGF-dependent migrant and invasive promotion of gastric cancer.…”
Section: Discussionsupporting
confidence: 72%
“…Our prior studies had found multiple genes and signaling pathways participated or play dominant role in tumorigenic process of gastric cancer, such as HGF, which secreted by cancer-associated fibroblasts, could promote vascularization in gastric cancer via activating PI3K/Akt and ERK1/2 signaling pathway [2], and accelerated proliferation, migration and invasion of MET-unamplified gastric cancer cells through activating c-MET/Stat3/twist1 signaling pathway [3]. It was noteworthy that HGF-c-MET signaling pathway is activated in a range of cancer types including gastric cancer, colorectal cancer, head and neck cancer, hepatocellular carcinoma, lung cancer, urothelial carcinoma of bladder, glioblastoma, melanoma and ovarian cancer, among others [2,[4][5][6][7][8][9][10][11], and associated with an aggressive phenotype and poor prognosis in pancreatic cancer [12].…”
Section: Introductionmentioning
confidence: 99%
“…HGF reportedly enhances the invasive capacity of cancer cells . Our clinicopathological analysis revealed that the frequency of vascular invasion and/or pleural invasion (local invasion) was significantly higher in the cases with CAFs‐CM induced gefitinib resistance (Table a).…”
Section: Discussionmentioning
confidence: 75%
“…Digging deeper into the complex interactions and cross‐talk between cancer cells and their associated microenvironment therefore holds the potential to reveal actionable targets in this devastating subtype. For example, cross‐talk between CAF or bone marrow‐derived myofibroblasts and GC cells has been reported to maintain GC stemness and invasiveness with critical involvement of transforming growth factor beta signaling, while CAF‐derived HGF was found to induce tumorigenesis and metastasis of MET ‐unamplified GC . Ascertaining the intratumoral stromal proportion and characterization of the molecular features may thus prove useful in therapeutic development.…”
Section: Confounding Layers Of Complexities Underlie Gc Classificationmentioning
confidence: 99%